2022
DOI: 10.1155/2022/4807175
|View full text |Cite|
|
Sign up to set email alerts
|

The Value of Rivaroxaban Combined with Ticagrelor in Antithrombotic Therapy after PCI in Patients with Nonvalvular Atrial Fibrillation with Acute Coronary Syndrome

Abstract: Objective. Based on a retrospective cohort study, to investigate the value of rivaroxaban combined with ticagrelor in antithrombotic therapy after PCI in patients with nonvalvular atrial fibrillation with acute coronary syndrome. Methods. A total of 60 patients from January 2019 to May 2021 accepted therapy with antithrombotic therapy after PCI. The patients treated with ticagrelor were set as the control group, and those given rivaroxaban combined with ticagrelor were set as the research group. The curative e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%